The Relationship between Body Image Coping Strategy and Eating Disorders among Iranian Adolescent Girls - Farid, Malihe; Kamrani, Mahnaz Akbari (BALI MEDICAL JOURNAL, 2016)
Background: Due to physical and psychological changes during puberty, most common problem of young people is body image defined as degree of size, shape and general appearance. Wrong perception of body image and dissatisfaction with body image in people can lead to eating disorders and stress. Peace of mind is in fact a mental mechanism that people use it to reduce physical and emotional strains coping with stressful situations. The aim of this study was to determine the type of coping strategy of adolescent girls and its relationship with their eating disorders. Methods: This is study is a cross-sectional study in which 573 female adolescent of Karaj participated. Two-Stage Random Sampling was used in this study. In this study, to assess people who are at risk of eating disorder, the nutritional approach assessment questionnaire of EAT-26 was used, while Strategy Inventory Body Image Coping- BICSI questionnaire was used to determine the type of coping strategy. Results: In this study, the mean age of participants was 16.6 (±1/62) (19- 14 years). In this study, 23.7% of participants had an eating disorder. Mental image of an individual of his body had significant correlation with eating disorder (P= 0.000). Kruskal-Wallis test showed a significant relationship between the type of coping strategy adopted by adolescent girls and eating disorder score of them (P= 0.007). The relationship between coping strategy and body image and having or not having the eating disorder was determined by Chi-square test at the borderline level (P= 0.054). Conclusion: In this study, results showed that there is relationship between coping strategy of adolescent girls and the eating disorder score of adolescent girls. The highest score was assigned to getting involved with body image, followed by avoidance and rational acceptance. Since the use of inappropriate coping strategies is associated with negative results such as eating disorders and depression, it is expected that eating disorders resulting from mental body image to be reduced by management of people in using correct and appropriate coping strategies.
Keywords: Adolescent girls, BMI, body image coping strategies, eating disorders